Genetic polymorphism of antioxidant enzymes in eosinophilic and non-eosinophilic nasal polyposis - Akyigit, Abdulvahap; Keles, Erol; Etem, Ebru Onalan; Ozercan, Ibrahim; Akyol, Hatice; Sakallioglu, Oner; Yalcin, Sinasi (Springer, 2017)
Chronic rhinosinusitis with nasal polyps (CRSwNP) is a chronic inflammatory disease of the paranasal sinuses, and its pathophysiology is not yet precisely known. It is suggested that oxygen free radicals play an important role in the pathogenesis of nasal polyposis. This study aimed to identify genetic polymorphisms of superoxide dismutase (SOD 2), catalase (CAT), and inducible nitric oxide synthase (iNOS) enzymes in eosinophilic CRSwNP and non-eosinophilic CRSwNP patients; the study also aimed to evaluate the effect of genetic polymorphism of antioxidant enzymes on CRSwNP etiopathogenesis. One hundred thirty patients, who received endoscopic sinus surgery due to CRSwNP, and 188 control individuals were included in this study. Nasal polyp tissues were divided into two groups histopathologically as eosinophilic CRSwNP and non-eosinophilic CRSwNP. Venous blood samples were taken from the patient and control groups. Polymorphisms in the Ala16Va1 gene, which is the most common variation of SOD-2 gene, and 21 A/T polymorphisms in catalase gene were evaluated with the restriction fragment length polymorphism method and -277 C/T polymorphism in the iNOS gene was evaluated with the DNA sequencing method. The GG genotype distribution for the (-277) A/G polymorphism in the iNOS gene was a statistically significant difference between eosinophilic CRSwNP and control groups (p < 0.05). The CC genotype distribution for the SOD2 A16V (C/T) polymorphism was not statistically significant in all groups (p > 0.05). The TT genotype distribution for the A/T polymorphism in catalase gene at position -21 was statistically significant differences in eosinophilic CRSwNP and control groups (p < 0.05). Increased free oxygen radical levels, which are considered effective factors in the pathogenesis of CRSwNP, can occur due to genetic polymorphism of enzymes in the antioxidant system and genetic polymorphism of antioxidant enzymes in eosinophilic CRSwNP patients might contribute to the pathophysiology.
Keywords: Chronic rhinosinusitis with nasal polyps; Inducible nitric oxide synthase; Superoxide dismutase; Catalase; Genetic polymorphism